Pengaruh Keaktifan Berorganisasi terhadap Perilaku Belajar Mahasiswa di Universitas Negeri Medan - Rachel Elisabet Ginting; Sani Susanti (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to determine the effect of organizational involvement on students’ learning behavior at Universitas Negeri Medan. The research is motivated by the observation that student participation in campus organizations may have both positive and negative impacts on academic learning. A quantitative method with an ex post facto approach was employed. A total of 163 students were randomly selected from the population of active members across 12 Student Activity Units (UKM). Data were collected using a closed-ended questionnaire with a Likert scale. The results showed that students' level of organizational activity was generally high, with the majority classified under the "high" category. Meanwhile, the learning behavior of students actively involved in organizations was categorized as "fairly good", with an average score of 79. Based on regression analysis, a negative and significant effect of 15.8% was found between organizational involvement and learning behavior. This means that the more active students are in organizational activities, the more likely their learning behavior declines. These findings highlight the importance of time management and academic awareness to help students balance organizational commitments with their learning responsibilities.